War and moral dissonance - French, Peter A. (Cambridge University Press, 2011)
This collection of essays, inspired by the author's experience teaching ethics to Marine and Navy chaplains during the Iraq War, examines the moral and psychological dilemmas posed by war. The first section deals directly with Dr Peter A. French's teaching experience and the specific challenges posed by teaching applied and theoretical ethics to men and women wrestling with the immediate and personal moral conflicts occasioned by the dissonance of their duties as military officers with their religious convictions. The following chapters grew out of philosophical discussions with these chaplains regarding specific ethical issues surrounding the Iraq War, including the nature of moral evil, forgiveness, mercy, retributive punishment, honour, torture, responsibility and just war theory. This book represents a unique viewpoint on the philosophical problems of war, illuminating the devastating toll combat experiences take on both an individual's sense of identity and a society's professed moral code